Pelatihan Built in Quality di PT. Asalta Mandiri Agung : Pengabdian - Istiqoomatun Nisaa; Sujana, Ujang; Sidik, Rasyid; Wisnu Nugroho, Haris; Rochmat; Putranto Widiatmoko, Roso (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Training in a does not only aim to deliver messages or training material, but also to make employees understand the training material and can apply it to the environment in which they work. In this study the authors observed that communication between instructors and training participants was not optimal. This can be seen from the assessment of the pre-test and post-test that has results that do not meet the standards set. The method used in this service is qualitative descriptive. To get complete information in accordance with the focus of the research, the data collection technique is used by means of interviews, observation and documentation. From the results of this study the communication strategy used by instructors to BIQ training participants is by determining the target of the training participants, composing messages, determining methods using the media.